Multi-objective optimal reactive power dispatch using multi-objective differential evolution. (November 2016) - Basu, M.
Highlights: This paper presents MODE to solve MORPD problem. MODE has been tested on IEEE 30-bus, 57-bus and 118-bus systems. Numerical results have been compared with those acquired from SPEA 2. Abstract: This paper presents multi-objective differential evolution (MODE) to solve multi-objective optimal reactive power dispatch (MORPD) problem by minimizing active power transmission loss and voltage deviation and maximizing voltage stability while varying control variables such as generator terminal voltages, transformer taps and reactive power output of shunt VAR compensators. MODE has been tested on IEEE 30-bus, 57-bus and 118-bus systems. Numerical results for these three test systems have been compared with those acquired from strength pareto evolutionary algorithm 2 (SPEA 2).